Answer:
2w + 2
Step-by-step explanation:
Width = w
Twice its width = 2*w =2w
2 inches more than twice its width = 2w + 2
Length = 2w + 2
After 20 months. after 20 months the first dealer will cost 5500 and the second dealer will cost 5500
dealer one pays 3000 in monthly fines and 2500 down and dealer 2 pays 2500 in fines and 300 down
3 dumplings can be made by Serenity
<em><u>Solution:</u></em>
Given that,
Serenity has
cups of dough to make dumplings
She uses
cup of dough for each dumpling
To find: Number of whole dumplings made
From given information,
![\text{Total cups of dough } = 2\frac{1}{2} = \frac{2 \times 2+1}{2} =\frac{5}{2}](https://tex.z-dn.net/?f=%5Ctext%7BTotal%20cups%20of%20dough%20%7D%20%3D%202%5Cfrac%7B1%7D%7B2%7D%20%3D%20%5Cfrac%7B2%20%5Ctimes%202%2B1%7D%7B2%7D%20%3D%5Cfrac%7B5%7D%7B2%7D)
![\text{Cups of dough for 1 dumpling } = \frac{3}{4}](https://tex.z-dn.net/?f=%5Ctext%7BCups%20of%20dough%20for%201%20dumpling%20%7D%20%3D%20%5Cfrac%7B3%7D%7B4%7D)
To find the number of whole dumplings made, we can divide the total cups of dough by cups of dough for 1 dumpling
![\text{Number of whole dumplings made } = \frac{\text{total cups of dough}}{\text{cups of dough for 1 dumpling}}\\\\\text{Number of whole dumplings made } = \frac{\frac{5}{2}}{\frac{3}{4}} = \frac{5}{2} \times \frac{4}{3}\\\\\text{Number of whole dumplings made } = \frac{10}{3} = 3.33 \approx 3](https://tex.z-dn.net/?f=%5Ctext%7BNumber%20of%20whole%20dumplings%20made%20%7D%20%3D%20%5Cfrac%7B%5Ctext%7Btotal%20cups%20of%20dough%7D%7D%7B%5Ctext%7Bcups%20of%20dough%20for%201%20dumpling%7D%7D%5C%5C%5C%5C%5Ctext%7BNumber%20of%20whole%20dumplings%20made%20%7D%20%3D%20%5Cfrac%7B%5Cfrac%7B5%7D%7B2%7D%7D%7B%5Cfrac%7B3%7D%7B4%7D%7D%20%3D%20%5Cfrac%7B5%7D%7B2%7D%20%5Ctimes%20%5Cfrac%7B4%7D%7B3%7D%5C%5C%5C%5C%5Ctext%7BNumber%20of%20whole%20dumplings%20made%20%7D%20%3D%20%5Cfrac%7B10%7D%7B3%7D%20%3D%203.33%20%5Capprox%203)
Thus 3 dumplings can be made
9514 1404 393
Answer:
d. 14 -3x
Step-by-step explanation:
If you want to substitute for y in the second equation, you must use the first equation to find an expression for y.
3x +y = 14 . . . . . . first equation
y = 14 -3x . . . . . . subtract 3x from both sides
This gives you the expression for y that you want to use for substitution. It matches the expression of choice D.
y = 14 -3x . . . . matches D
Answer: A
Step-by-step explanation:
#![GameOn](https://tex.z-dn.net/?f=GameOn)